Diseño de infraestructura para mejorar el circuito de ventilación de la veta rosa - zona norte en consorcio minero horizonte, Pataz 2018 - Diaz Avalos, Roberto Carlos (2018)
The Parcoy mine has been exploited years ago in a conventional way in its high parts with an infrastructure of reduced sections (chimneys, galleries and cruises) which are today limiting the entry of clean air and the outflow of stale air for current operations in depth , this added to restrictions to avoid the entry of third parties, have made the mine close mouths limiting even more the flow and at the moment it does not have the flow and pressure necessary for the system. Under current conditions, the flow of clean air required in the North Zone, Veta Rosa is 263,249 cfm., However, the current clean air flow rate is only 134,200 cmf. Having a deficit of 126,473 cfm. which represents an air coverage of 52%. In order to achieve 100% air coverage, it has been proposed to execute the "integral infrastructure project for ventilation of the Rosa vein", which envisages the execution of trunk 2, of 595 m. of Alimak chimneys from the NV2650 (from surface) to the NV2140, which will be for evacuation of stale air, additional to trunk 1 that already exists. It is also proposed to run chimneys for the entrance of clean air located at the roof of the vein, 420 m. of Alimak Chimneys from the NV2500 to the NV2240. With the execution of the project, it would have a flow of clean air income of 329,822 cfm, which represents an air coverage of 103%.